Question
upstudy study bank question image url

The vertices of a quadrilateral are \( \mathrm{K}(-1,3) \) and 6. \( L(2,3) \) and \( Q(6,-3) \) and \( R(m-1, n-2) \) if \( |K L|=|R Q| \) find \( m \) and \( n \)

Ask by Bradley Ingram. in Ghana
Nov 05,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

The values of \( m \) and \( n \) are: - \( m = 4, n = -1 \) - \( m = 7, n = 2 \) - \( m = 10, n = -1 \) - \( m = 7, n = -4 \) - \( m = 5, n = 1 \) - \( m = 5, n = -3 \) - \( m = 9, n = 1 \) - \( m = 9, n = -3 \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

The Deep Dive

First, we need to find the distance \( |KL| \) between points \( K(-1, 3) \) and \( L(2, 3) \). The formula for distance between two points \( (x_1, y_1) \) and \( (x_2, y_2) \) is given by: \[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \] Applying the coordinates of \( K \) and \( L \): \[ |KL| = \sqrt{(2 - (-1))^2 + (3 - 3)^2} = \sqrt{(2 + 1)^2 + 0} = \sqrt{3^2} = 3 \] Now we are given that \( |KL| = |RQ| \). Next, we need to find \( |RQ| \) between points \( R(m-1, n-2) \) and \( Q(6, -3) \): \[ |RQ| = \sqrt{(6 - (m-1))^2 + (-3 - (n-2))^2} \] This can be simplified to: \[ |RQ| = \sqrt{(6 - m + 1)^2 + (-3 - n + 2)^2} = \sqrt{(7 - m)^2 + (-1 - n)^2} \] Setting this equal to the distance |KL|: \[ \sqrt{(7 - m)^2 + (-1 - n)^2} = 3 \] Squaring both sides gives: \[ (7 - m)^2 + (-1 - n)^2 = 9 \] Now we expand this equation: \[ (7 - m)^2 + (n + 1)^2 = 9 \] Let’s solve this equation step by step. First, we can set \( (7 - m) = a \) and \( (n + 1) = b \), leading to: \[ a^2 + b^2 = 9 \] This represents a circle with radius \( 3 \) centered at the origin in terms of \( a \) and \( b \). We can find specific integer solutions. For simplicity, let’s evaluate cases where \( a \) and \( b \) can yield integer squares. 1. If \( a = 0 \), then \( b^2 = 9 \Rightarrow b = 3 \) or \( b = -3 \) - \( 7 - m = 0 \Rightarrow m = 7 \) and \( n + 1 = 3 \Rightarrow n = 2 \) → solution: \( (m, n) = (7, 2) \) - \( 7 - m = 0 \Rightarrow m = 7 \) and \( n + 1 = -3 \Rightarrow n = -4 \) → solution: \( (m, n) = (7, -5) \) 2. If \( a = 3 \), then \( b^2 = 0 \Rightarrow b = 0 \) - \( 7 - m = 3 \Rightarrow m = 4 \) and \( n + 1 = 0 \Rightarrow n = -1 \) → solution: \( (m, n) = (4, -1) \) 3. If \( a = -3 \), then \( b^2 = 0 \Rightarrow b = 0 \) - \( 7 - m = -3 \Rightarrow m = 10 \) and \( n + 1 = 0 \Rightarrow n = -1 \) → solution: \( (m, n) = (10, -1) \) 4. If \( a = 2 \) or \( a = -2 \), we can find similar assignments giving other integer pairs based on the squares. Verifying these: We can take pairs [\( (m, n) (7, 2) ,( 4, -1), (10, -1) \)]. Lastly, one valid solution for \( (m, n) = (4, -1) \) is commonly accepted after ensuring all conditions are intact. Thus, the value of \( m \) and \( n \) could be: \[ m = 4, \; n = -1 \] or others depending on the integer conditions. Final solutions, you can pick your pair!

Related Questions

Latest Geometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy